The Influence of Health Education Using Animated Video Media on Mothers’ Knowledge About Developmental Stimulation of Toddlers Aged 36-60 Months at Nurul Huda PAUD, Karangbesuki, Sukun District, Malang City - Vivi Tiara Putri; Ibnu Fajar; Sugijati Sugijati; Gita Kostania (International Journal Of Health Science, 2026)
Mothers’ knowledge about toddler development is very important because it can affect the way they provide stimulation to toddlers. Based on the results of a preliminary study through interviews with mothers of toddlers at PAUD Nurul Huda, it was found that 6 out of 11 mothers said they did not know about stimulation and had never received information about developmental stimulation in toddlers. One effort to improve mothers’ knowledge is to provide health education using animated videos about developmental stimulation in toddlers. The purpose of this study was to determine the effect of health education using animated video media on mothers’ knowledge about developmental stimulation in toddlers aged 36-60 months. The research design was a pre-experimental study with a one group pre-test post-test approach, with a population of 33 mothers, with sampling using a total sampling technique with a total of 33 mothers who had toddlers aged 36-60 months. The research instrument used a questionnaire and also media in the form of animated videos. Before the intervention was given, most (72.7%) mothers had sufficient knowledge, after the intervention was given, most (78.8%) mothers had good knowledge. Bivariate analysis using the Wilcoxon Signed Rank Test, and obtained a ρ-value of 0.000 < (ɑ = 0.05). The conclusion of this study is that there is a significant influence of health education using animated videos on mothers’ knowledge about stimulating the development of toddlers aged 36-60 months at PAUD Nurul Huda.